2007
DOI: 10.1017/s0016672307008701
|View full text |Cite
|
Sign up to set email alerts
|

Linked and pleiotropic QTLs influencing carcass composition traits detected on porcine chromosome 7

Abstract: A multivariate QTL detection was carried out on fatness and carcass composition traits on porcine chromosome 7 (SSC7). Single-trait QTLs have already been detected in the SLA region, and multivariate approaches have been used to exploit the correlations between the traits to obtain more information on their pattern: almost 500 measurements were recorded for backfat thickness (BFT1, BFT2), backfat weight (BFW) and leaf fat weight (LFW) but only about half that number for intramuscular fat content (IMF), affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
2
15
1
Order By: Relevance
“…Thus, 68% of the animals are carriers of at least one unfavorable haplotype and almost 4% of the pigs carry two copies of the most unfavorable haplotype. In addition, although meat quality traits had only moderate phenotypic correlations with growth or intake traits in our study, meat quality traits are known to have antagonistic relationships with feed efficiency traits [50]. Such antagonistic effects were, however, not found for these haplotypes or for any of the significant SNPs for meat quality and either FCR or RFI.…”
Section: Discussioncontrasting
confidence: 69%
“…Thus, 68% of the animals are carriers of at least one unfavorable haplotype and almost 4% of the pigs carry two copies of the most unfavorable haplotype. In addition, although meat quality traits had only moderate phenotypic correlations with growth or intake traits in our study, meat quality traits are known to have antagonistic relationships with feed efficiency traits [50]. Such antagonistic effects were, however, not found for these haplotypes or for any of the significant SNPs for meat quality and either FCR or RFI.…”
Section: Discussioncontrasting
confidence: 69%
“…It may be of interest, particularly in this latter case, to distinguish linkages from pleiotropies in order to know whether there is any possibility of breaking down the unfavourable associations. More complex multivariate models can be used to test the hypothesis of linkage v. pleiotropy, as recently shown by Gilbert et al (2007). Increasing the accuracy of QTL location through fine-mapping programmes using recombinant backcrosses and/or highly dense sets of SNP markers in different populations would also be helpful to answer such questions and increase the efficiency of marker-assisted selection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some authors (e.g. Gilbert et al, 2007) concluded pleiotropic and linked QTL effects on porcine carcass.…”
Section: Resultsmentioning
confidence: 99%